Review Pengaruh Jenis Material Atap terhadap Efisiensi Pemanenan Energi dengan Piezoelektrik sebagai Konverter Energi Mekanik menjadi Energi Listrik - Muhammad Fahmi Nurhidayat; Rifky; Kurnia Sandi Oktaris; Pandu Kusuma Pangestu; Reyhan Martin Firnanda; M. Ravi Cahya Firdaus (Prosiding Seminar Nasional Teknoka, 2025)
Raindrops hitting the roof material and the falling rainwater exerting pressure on the roof can be utilized as a power source with piezoelectrics as a converter of mechanical energy into electrical energy. The purpose of this research is to find the right roof material to produce maximum electrical power and efficiency in harvesting the energy of falling rainwater. This research method is carried out by comparing three types of roof materials placed on top of the piezoelectric. The falling rainwater will press the roof material and piezoelectric, thus producing electricity in the form of voltage and current measured with a multitester. The measurement data is processed into electrical power and efficiency. The results of the study found that the type of roof material affects the performance of the piezoelectric as an energy converter.